Evaluasi Pembelajaran Berbasis Information and Communication Technology (ICT) pada Mata Pelajaran PAI - Fajri, Yusron Al; Sahlan, Mohammad (PT The Collaboration UVW, 2023)
Computer-based information technology is a means of delivering and processing information using micro-processors. In the context of learning evaluation, the implementation of ICT-based learning evaluation in PAI subjects at the senior high school level is a form of learning evaluation that uses the Computer Based Test (CBT) model, where CBT itself is also part of the application of Information and Communication Technology (ICT). The implementation of ICT-based evaluation in PAI subjects is no longer using paper, but the test can be done directly on the computer and the scoring system is also directly managed by the system, so that the presence of ICT-based learning evaluation in PAI subjects is able to provide convenience for educators and can advance the world of education at the pace of technological and information development.